2016
DOI: 10.1007/s00405-016-4358-x
|View full text |Cite
|
Sign up to set email alerts
|

Rhinophototherapy in persistent allergic rhinitis

Abstract: Previous published results have revealed that Rhinolight intranasal phototherapy is safe and effective in intermittent allergic rhinitis. The present objective was to assess whether phototherapy is also safe and effective in persistent allergic rhinitis. Thirty-four patients with persistent allergic rhinitis were randomized into two groups; twenty-five subjects completed the study. The Rhinolight group was treated with a combination of UV-B, UV-A, and high-intensity visible light, while the placebo group recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 25 publications
0
16
0
4
Order By: Relevance
“…A number of researchers believe that a variety of inflammatory mediators may play important roles in the pathogenesis of allergic rhinitis (19), such as IL-17A and IL-6. As an important member of the IL-17 family, IL-17A could induce the activation of T cells, activate protein kinases, regulate the activity of kinases, play an important role in signaling pathways (such as P38-mitogen-activated protein kinase), and stimulate the release of various inflammatory factors, such as IL-6 and IL-8, thereby triggering a series of inflammatory airway response (9).…”
Section: Discussionmentioning
confidence: 99%
“…A number of researchers believe that a variety of inflammatory mediators may play important roles in the pathogenesis of allergic rhinitis (19), such as IL-17A and IL-6. As an important member of the IL-17 family, IL-17A could induce the activation of T cells, activate protein kinases, regulate the activity of kinases, play an important role in signaling pathways (such as P38-mitogen-activated protein kinase), and stimulate the release of various inflammatory factors, such as IL-6 and IL-8, thereby triggering a series of inflammatory airway response (9).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that intranasal irradiation using Rhinolight (Rhinolight Ltd., Szeged, Hungary), which contains visible light (70%), UVA (25%) and UVB (5%) was effective for AR treatment 19,20 . It has also been reported that Rhinolight induced apoptosis of T cells and eosinophils in the nasal mucosa, and decreased levels of IL‐5 and eosinophilic cationic protein in the nasal discharge 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Devices beaming inside the nose certain wavelengths of visible and infrared light have been shown to reduce the symptoms and improve HRQoLin subjects with allergic rhinitis to both outdoor and indoor allergens. 187 , 188 , 189 , 190 …”
Section: Devices Used For Treatmentmentioning
confidence: 99%